Climate Change Influences on the Global Potential Distribution of the Mosquito Culex quinquefasciatus, Vector of West Nile Virus and Lymphatic Filariasis. - Abdallah M Samy; Arwa H Elaagip; Mohamed A Kenawy; Constância F J Ayres; A Townsend Peterson; Doaa E Soliman (PLoS ONE, 2016)
Rapid emergence of most vector-borne diseases (VBDs) may be associated with range expansion of vector populations. Culex quinquefasciatus Say 1823 is a potential vector of West Nile virus, Saint Louis encephalitis virus, and lymphatic filariasis. We estimated the potential distribution of Cx. quinquefasciatus under both current and future climate conditions. The present potential distribution of Cx. quinquefasciatus showed high suitability across low-latitude parts of the world, reflecting the current distribution of the species. Suitable conditions were identified also in narrow zones of North Africa and Western Europe. Model transfers to future conditions showed a potential distribution similar to that under present-day conditions, although with higher suitability in southern Australia. Highest stability with changing climate was between 30°S and 30°N. The areas present high agreement among diverse climate models as regards distributional potential in the future, but differed in anticipating potential for distribution in North and Central Africa, southern Asia, central USA, and southeastern Europe. Highest disparity in model predictions across representative concentration pathways (RCPs) was in Saudi Arabia and Europe. The model predictions allow anticipation of changing distributional potential of the species in coming decades.